Does the Covid-19 Pandemic Affect International Tourism in Indonesia? - Fazzaalloh, Al Muizzuddin; Prestianawati, Silvi Asna; Asyrof, Rifqi Aqil; Fawwaz, Muhammad (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2024)
The tourism sector is one of the sectors most affected by the spread of COVID-19. The policy of restricting the mobilization of citizens caused a major collapse in the tourism sector both at the domestic and international levels. Restrictions on people's mobilization led to the suspension of travel by land, sea and air and if it lasts for a long time, these companies will certainly suffer financially. In this study, the author considers how international tourism in ASEAN Countries is affected by Covid-19 and whether it causally affects each other. Some countries such as Thailand and Vietnam are taking uncertain steps about reopening the economy for business and social operations. ASEAN countries are the focus of this research because ASEAN countries, especially Southeast Asian countries, have a higher increase in COVID-19 cases than other countries. In analyzing the impact of the Covid-19 pandemic on the number of foreign tourist arrivals from ASEAN countries in Indonesia, the author uses data from the Central Statistics Agency (BPS) accessed from https://www.bps.go.id/ and data on the Covid-19 pandemic we access from https://covid.ourworldindata.org/data/latest/owid-covid-latest.csv. The author uses monthly data from the 3rd month period of 2020 to the 12th month of 2022. The dependent variable used in this study is foreign tourist arrivals from ASEAN countries, where the ASEAN countries are Brunei Darussalam, Malaysia, Philippines, Singapore, Thailand, Vietnam, Laos, Cambodia, and Myanmar. While the independent variable is the Covid-19 pandemic which is proxied through four variables, namely: total cases, new cases, new deaths, new vaccinations. Then, the income per capita variable is the control variable in this study.